2018
DOI: 10.1212/nxg.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of pediatric movement disorders and management implications

Abstract: ObjectiveTo identify underlying genetic causes in patients with pediatric movement disorders by genetic investigations.MethodsAll patients with a movement disorder seen in a single Pediatric Genetic Movement Disorder Clinic were included in this retrospective cohort study. We reviewed electronic patient charts for clinical, neuroimaging, biochemical, and molecular genetic features. DNA samples were used for targeted direct sequencing, targeted next-generation sequencing, or whole exome sequencing.ResultsThere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 25 publications
3
35
2
Order By: Relevance
“…Diagnostic rates were relatively higher in cohorts with only paediatric patients and with the use of WES. Comparing with studies using targeted NGS approach with a diagnostic rate range from 11-28%, our study and Cordeiro et al (19) with WES has a higher diagnostic rate of 32% and 51% respectively. Further looking into the diagnoses, two (2/10, 20%) and six (6/26, 23%) in our cohort and Cordeiro et al's cohort can be made by WES only.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Diagnostic rates were relatively higher in cohorts with only paediatric patients and with the use of WES. Comparing with studies using targeted NGS approach with a diagnostic rate range from 11-28%, our study and Cordeiro et al (19) with WES has a higher diagnostic rate of 32% and 51% respectively. Further looking into the diagnoses, two (2/10, 20%) and six (6/26, 23%) in our cohort and Cordeiro et al's cohort can be made by WES only.…”
Section: Discussionsupporting
confidence: 50%
“…Most of the previous studies in MDs patient cohorts had not investigated the therapeutic potentials based on the genetic diagnosis. Only the study of Cordeiro et al (19) suggested that 38% of their patients with genetic diagnoses had treatment implications (Table 3). With the growth of new treatment strategies emerging in recent years, genetic testing becomes even more crucial to direct genotype-targeted therapies in MDs.…”
Section: Potential Genotype-targeted Treatment Implicationsmentioning
confidence: 99%
“…3 Our diagnostic yield was at the same level as other smaller exome sequencing studies of symptom-based pediatric ataxia (46%-80%). 7,8,23 The percentage of genetically diagnosed patients that were found to have a de novo variant underlying their disease in previous studies varied. In the first such published study, 7 in a cohort of 28 families (6 consanguineous), 9% had a pathogenic de novo variant.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a remarkably higher de novo rate of 45% in patients with previously molecularly undiagnosed childhoodonset ataxia. Other reports include a 25% de novo rate in a study that investigated congenital ataxia in consanguineous families 8 and another study 23 that found a 42% de novo rate in a pediatric movement disorder cohort including patients with ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the distinct pathway involved, IEMs can be categorized as described by the nosology of Ferreira et al into the following groups (1): (1) Disorders of nitrogen-containing compounds, (2) Disorders of vitamins, cofactors, metals, and minerals, (3) Disorders of carbohydrates, (4) Mitochondrial disorders of energy metabolism, (5) Disorders of lipids, (6) Disorders of Tetrapyrroles, (7) Storage disorders, (8) Disorders of peroxisome and oxalate, and (9) Congenital disorders of glycosylation. This accurate and updated nosology will be applied in this review, in which a total of 231 IEMs presenting with MD will be included.…”
Section: Overview Of Movement Disorders In Inborn Errors Of Metabolismmentioning
confidence: 99%